Innovative Approaches to Community-Based Social Work: Building Resilience against Climate Change Impacts - Hafiz Muhammad Sarmad Abid; Dr Nosheen Raza; Maryam Naz; Tehreem Bukhari, (Dialogue Social Science Review (DSSR), 2025)
Climate change generates extensive challenges which mainly affect vulnerable populations along with those who face marginalization across different communities worldwide. Without enough resources and infrastructure these communities become highly exposed to environmental disruptions which affects them negatively. This paper examines advanced CBSW tactics that develop climate change resistance abilities. CSBW professionals help communities adapt to and combat climate disruptions through sustainable environmental practices and social assistance which allows them to overcome these climate threats in a thriving fashion. CBSW utilizes participatory planning with capacity-building programs alongside policy advocacy to establish strong structures which handle short-term and long-range environment and social concerns. Community resiliency requires local people to work together with specialists from different fields who adopt indigenous wisdom in their planning efforts. The main approaches presented in this paper advance comprehensive climate resilience strategies for local communities which empower vulnerable populations to handle the unpredictable climate changes. CBSW methods concentrate on social fairness while guaranteeing equal access for those who need help through approaches that maintain cultural sensitivity. Sustainable development emerges within communities through this initiative which both deals with present climate challenges and equips communities to face an uncertain future while safeguarding environmental health.